COVID-19 in Pediatric Granulomatosis with Polyangiitis - Amir Saeed; Eslam Shorafa; Zahra Seratishirazi; Seyedenarjes Abootalebi (MDPI AG, 2021)
The confirmed cases with COVID-19 in children account for just 1% of the overall confirmed cases. Severe COVID-19 in children is rare. Case Presentation: Our patient was 16 years old with a severe case of COVID-19 and did not survive due to the presence of Granulomatosis with polyangiitis and being treated with immunosuppressive drugs. We used lopinavir, ritonavir, hydroxy chloroquine, intravenous immunoglobulin and continuous veno-venous hemodialysis for treatment. Conclusion: In this patient, an underlying disease and delayed admission to the hospital were two factors complicating his condition.